2018
DOI: 10.1111/jfd.12812
|View full text |Cite
|
Sign up to set email alerts
|

Xanthine oxidase activity exerts pro‐oxidative and pro‐inflammatory effects in serum of silver catfish fed with a diet contaminated with aflatoxin B1

Abstract: Several studies have associated the involvement of xanthine oxidase (XO) activity, a source of uric acid and reactive oxygen species (ROS), to pro-oxidative and pro-inflammatory effects during pathological conditions. Considering this, the aim of this study was to evaluate whether upregulation on seric XO activity may be a pathway involved in the oxidative stress in fish exposed to a diet contaminated with aflatoxin B (AFB ), as well as whether it may be considered a pathway involved in ROS and NOx production.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Based on these data, it is also reasonable to hypothesize that AOH, AS, and α-ZEL are not able to disrupt the XO-mediated biotransformation of 6mercaptopurine or other drugs (e.g., azathioprine). Considering the previous observations in animal studies [30][31][32][33][34], some mycotoxins may be able to induce the increased expression of XO, which likely have more in vivo relevance than the inhibitory effects noticed in the current study.…”
Section: Inhibitory Effects Of Mycotoxins On Xanthine Oxidase Enzymesupporting
confidence: 57%
See 1 more Smart Citation
“…Based on these data, it is also reasonable to hypothesize that AOH, AS, and α-ZEL are not able to disrupt the XO-mediated biotransformation of 6mercaptopurine or other drugs (e.g., azathioprine). Considering the previous observations in animal studies [30][31][32][33][34], some mycotoxins may be able to induce the increased expression of XO, which likely have more in vivo relevance than the inhibitory effects noticed in the current study.…”
Section: Inhibitory Effects Of Mycotoxins On Xanthine Oxidase Enzymesupporting
confidence: 57%
“…Previous studies demonstrated that aflatoxins and ochratoxins could cause the development of gout in certain animals [30]. AFB1-contaminated diet (for 14 days and 21 days) increased XO activity and uric acid levels in the serum of fish [31]. In rats, chronic exposure to ZEN significantly elevated XO activity in the liver and kidneys [32].…”
Section: Cereals and Corresponding Productsmentioning
confidence: 96%
“…In fact, Lai and colleagues have recently reported that levels of AAMU are significantly increased in the serum of active CD compared with inactive CD patients and the control group. During the metabolism of caffeine, xanthine oxidoreductase catalyses paraxanthine to xanthine, which is oxidized in uric acid [100]. Interestingly, Neubauer and colleagues have recently analysed the levels of uric acid in serum of both UC and CD patients, and they reported significantly lower levels only in both active CD and active UC patients compared with control groups.…”
Section: Food Components and Xenobioticsmentioning
confidence: 99%
“…During the metabolism of caffeine in purine metabolism, xanthine oxidoreductase catalyzes paraxanthine to xanthine (Baldissera et al, 2018), which is in turn oxidized to uric acid. Uric acid induces the production and release of pro‐oxidants such as reactive oxygen species, proinflammatory mediators such as nitrogen oxide, and inflammatory cytokines, which cause inflammation.…”
Section: Discussionmentioning
confidence: 99%